Advances in Common Eye Infections - Rumelt, Shimon (IntechOpen, 2016)
This book is a new addition for a broad-spectrum library in ophthalmology and other specialties in medicine of "InTech." It addresses ocular infections. These infections may result in blindness if not correctly diagnosed and promptly treated. Therefore, it is essential to be fully aware and knowledgeable about the manifestations of these diseases, and this book covers some of the different aspects of them. The chapters were written by experts from around the globe and these reflect the importance of the subject. The book is aimed for ophthalmologists, residents in ophthalmology and infectious diseases, general practitioners, and researchers in hope to advance the knowledge for the benefit of the world habitants wherever they are.